# Thread: Need some help with simple problem.

1. ## Need some help with simple problem.

"Tyler writes this equation to solve a problem:

3(b - 4) = 9 + 6b,

He divides both sides of the equation by 3 to get

b - 4 = 3 +2b

so he concludes that

b= -7."

Okay, well with my math, I did the divide by 3 on both sides, and got

b-4 = 9+ 6b
-------
3

Not sure if I'm right or not.. anyone.. help please!

2. ## Re: Need some help with simple problem.

$3(b - 4) = 9 + 6b$

Dividing both sides by 3 gives

$\frac{3(b - 4)}{3} = \frac{9 + 6b}{3}$

Which simplifies to

$b - 4 = \frac{9 + 6b}{3}$

and then,

$b - 4 = \frac{9 }{3}+ \frac{ 6b}{3}$

$b - 4 = 3+ 2b$

continue...

3. ## Re: Need some help with simple problem.

Originally Posted by pickslides
$3(b - 4) = 9 + 6b$

Dividing both sides by 3 gives

$\frac{3(b - 4)}{3} = \frac{9 + 6b}{3}$

Which simplifies to

$b - 4 = \frac{9 + 6b}{3}$

and then,

$b - 4 = \frac{9 }{3}+ \frac{ 6b}{3}$

$b - 4 = 3+ 2b$

continue...
Oh okay. So the original way "Tyler" did it is correct.

Edit: Actually, he's not correct. The answer is -8, am I correct?

4. ## Re: Need some help with simple problem.

$b - 4 = 3+ 2b$

Take 3 from both sides.

$b - 7 = 2b$

Take b from both sides

$- 7 = b$